CircSCAP interacts with SF3A3 to inhibit the malignance of non-small cell lung cancer by activating p53 signaling - Chen, Dongni; Zhou, Hongli; Cai, Zhuochen; Cai, Kaican; Liu, Ji; Wang, Weidong; Miao, Huikai; Li, Hongmu; Li, Rongzhen; Li, Xiaodong; Chen, Youfang; Wang, Hui-Yun; et al. (Journal of experimental & clinical cancer research, 2022)
Circular RNA (circRNA) has been recently identified as a critical regulator during carcinogenesis. However, the biological function and potential underlying mechanisms of circRNAs in lung cancer remain to be further elucidated. Here, we first evaluated the differentially expressed circRNAs between tumor and the matched adjacent nontumor tissues (3 pairs) of lung cancer patients via circRNA microarray. The expression of top five dysregulated circRNAs were tested in lung cancer cell lines and the circSCAP with concordant alteration in microarray data and cell lines was selected for further investigation. Then we validated the expression level of circSCAP in tumor and corresponding adjacent tissues (161 pairs) from a lung cancer cohort by RT-PCR analysis followed by correlation and prognosis analysis between circSCAP and clinical characteristics. Non-small cell lung cancer (NSCLC) accounts for the majority of lung cancer diagnosis (about 80% in the cohort used in this study). Therefore, we focused the role of circSCAP in NSCLC in the present study. In vitro and in vivo assays were performed to study the biological function of circSCAP in NSCLC. Biotin-labeled RNA pulldown and RNA immunoprecipitation (RIP) assays were carried out to identify the proteins directly interacting with circSCAP. The molecular mechanism of circSCAP-driven tumor suppression was demonstrated by immunoblotting, immunoprecipitation and luciferase reporter assays. In vitro and in vivo rescue experiments were conducted to verify the role of the circSCAP/SF3A3/p53 signaling axis in NSCLC. We screened the expression profiles of human circRNAs in lung cancer tissues and found that hsa_circ_0065214 (termed as circSCAP) was significantly decreased. Kaplan-Meier analysis showed that patients with low level of circSCAP had a significantly poor prognosis. Gain- and loss-of-function experiments suggested that circSCAP played an important role in NSCLC cell proliferation, cell migration and apoptosis. Mechanistically, circSCAP directly binds to the SF3A3 protein, facilitating the reduction of SF3A3 by promoting its ubiquitin-proteasome-mediated degradation, which enhances the expression of MDM4-S to finally activate its downstream p53 signaling. These findings illustrate a novel circSCAP/SF3A3/p53 signaling axis involved in suppressing the malignance of NSCLC and provide a promising target for NSCLC prognosis prediction and treatment.